Deregulation of Provision of Educational Services and Quality of Staff, Facilities for Effective Teaching and Learning in Nigerian Universities - Ategwu, Emeka (NIU Journal of Humanities, 2022)
This work is centered on Deregulation of provision of educational services and quality of staff, facilities for effective teaching and learning in Nigerian universities. The purpose of the study is to investigate the impact of the deregulation of provision of educational service and quality of staff in both public and private universities, standard of facilities available for effective teaching and learning. Two research questions and two hypotheses guided the study. Data were elicited based on the following variables as they relate to ensuring quality of staff, quality of facilities. The theoretical framework of the study is based on public interest theory of deregulation, the design of the study is ex-post facto while the population of the study is all academic administrators in both public and private universities in the study area, and the sample size is 714. Questionnaire titled: â€œDeregulation of provision of Provision of Educational Services and Quality Assurance in Nigerian Universitiesâ€ is the main instrument used for generating data. The instrument was subjected to scrutiny by three experts. T-test statistic was used to test the two null hypotheses at 0.05 level of significance. The results show that there is a significant difference in the mean rating of academic administrators in public and private universities in deregulation of educational services on quality of staff and provision of educational services in quality of facilities for effective teaching and learning in Nigerian universities. This is to say that some have qualitative facilities while others have not. (especially public universities). Keywords: Deregulation, Educational Services, Quality of Staff, Facilities for effective teaching and learning, Nigerian Universities.